Contagious stablecoins? - Hugo van Buggenum; Hans Gersbach; Sebastian Zelzner (Goethe University Frankfurt, Center for Financial Studies (CFS), 2024)
Can competing stablecoins produce efficient and stable outcomes? We study competition among stablecoins pegged to a stable currency. They are backed by interest-bearing safe assets and can be redeemed with the issuer or traded in a secondary market. If an issuer sticks to an appropriate investment and redemption rule, its stablecoin is invulnerable to runs. Since an issuer must pay interest on its stablecoin if other issuers also pay interest, competing interest-bearing stablecoins, however, are contagious and can render the economy inefficient and unstable. The efficient allocation is uniquely implemented when regulation prevents interest payments on stablecoins.
Keywords: E4; E5; G1; G2; 330; Stablecoins; currency competition; free banking; private money; digital money